Influence of pedal foot position on muscular activity during ergometer cycling - Litzenberger, S.; Illes, S.; Hren, M.; Reichel, M.; Sabo, A. (The Engineering of sport 7, Volume 1, 2008)
Among cyclists it is a matter of common knowledge that the axis of the pedal has to be placed right beneath first metatarsal head at the forefoot (metatarsophalangeal position). Thus plantarflexion of the foot provides forces that result in evenly distributed crank-torque. Recent research has shown that even top cyclists neither deliver constant crank-torque nor flex the ankle excessively. Considering these facts and making biomechanical considerations it seems possible that much of the muscular Output of the lower limb is used exclusively to stabilize the ankle. Torque in the ankle joint is - due to the long lever arm - fairly high. Reducing this lever arm by placing the pedal beneath the metatarsus (tarsome-tatarsal position) reduces torque in the ankle-joint and thus reduces muscular activity in the lower limb. The present paper examines changes in muscular activity of eight selected muscles of the leg by changing the pedal-foot-position from metatarsophalangeal to tarso-metatarsal. Measurements were conducted on a bicycle ergometer (Daum, GER) at different power-outputs (75W, 150W) at two different pedal-foot-positions (metatarsophalangeal, tarsometatarsal) (N=12, non-cyclists). Muscular activity was recorded using an eight-channel-EMG-System (Noraxon, USA). Changes in muscular activity between different power Outputs and pedal-foot-positions are analysed. Results are that metatarsal pedalling reduces muscular effort for calf muscles up to more than 20%. Activation durations of thigh muscles do not channge significantly, frontal shank muscle activation duration rises remarkably. This and further research could ultimately result in the development of a new cycling-shoe construction.